2017
DOI: 10.1016/j.joms.2017.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Palatal Injection for the Removal of Maxillary Teeth: Current Practice Among Oral and Maxillofacial Surgeons

Abstract: Purpose:Conventional teaching regarding palatal injection for the removal of maxillary teeth dictates that both a buccal and palatal injection are to be administered. Recently, some authors have questioned the necessity of the palatal injection, suggesting that contemporary local anaesthetics might diffuse sufficiently across the buccal-palatal cortical bone distance. It has been suggested that since the buccal-palatal cortical bone distance increases anteriorly to posteriorly in the maxilla, the success of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Reason for exclusion Majid and Ahmed 2017 [25] palatal injection was given as a placebo Badenoch-Jones et al 2017 [26] cross-sectional study (survey) Badenoch-Jones et al 2016 [27] systematic review Hassan et al 2011 [32] less than 1.5 ml articaine administered Sharma et al 2014 [33] less than 1.5 ml articaine administered Badcock 2007 [34] cross-sectional study (survey) Khan and Qazi 2017 [40] only lidocaine used Bahrololoomi and Maghsoudi 2022 [41] conducted in pediatric clinics Gholami et al 2021 [42] less than 1.5 ml articaine administered Cui et al 2018 [44] meta-analysis Gazal 2020 [49] palatal injection of articaine Deshpande et al 2020 [50] less than 1.5 ml articaine administered Azad et al 2019 [52] less than 1.5 ml articaine administered Joshi and Soni 2019 [54] less than 1.5 ml articaine administered Shalash and Eladl 2019 [55] less than 1.5 ml articaine administered Friedl et al 2012 [22] less than 1.5 ml articaine administered Lima Jr et al 2009 [24] cross-sectional study Sekhar et al 2011 [30] only lidocaine used Isik et al 2011 [39] cross-sectional study…”
Section: Excluded Articlementioning
confidence: 99%
“…Reason for exclusion Majid and Ahmed 2017 [25] palatal injection was given as a placebo Badenoch-Jones et al 2017 [26] cross-sectional study (survey) Badenoch-Jones et al 2016 [27] systematic review Hassan et al 2011 [32] less than 1.5 ml articaine administered Sharma et al 2014 [33] less than 1.5 ml articaine administered Badcock 2007 [34] cross-sectional study (survey) Khan and Qazi 2017 [40] only lidocaine used Bahrololoomi and Maghsoudi 2022 [41] conducted in pediatric clinics Gholami et al 2021 [42] less than 1.5 ml articaine administered Cui et al 2018 [44] meta-analysis Gazal 2020 [49] palatal injection of articaine Deshpande et al 2020 [50] less than 1.5 ml articaine administered Azad et al 2019 [52] less than 1.5 ml articaine administered Joshi and Soni 2019 [54] less than 1.5 ml articaine administered Shalash and Eladl 2019 [55] less than 1.5 ml articaine administered Friedl et al 2012 [22] less than 1.5 ml articaine administered Lima Jr et al 2009 [24] cross-sectional study Sekhar et al 2011 [30] only lidocaine used Isik et al 2011 [39] cross-sectional study…”
Section: Excluded Articlementioning
confidence: 99%
“…387 To reduce the patients' discomfort, less and even minimally invasive local anesthesia techniques have been suggested. [387][388][389][390][391][392] The buccal and palatal infiltration of a local anesthetic has been taught to be the technique of choice to obtain appropriate numbness when performing dental extractions in the maxilla. 393 Especially, the palatal injection site causes significant pain.…”
Section: Oral Medicine and Oral Surgerymentioning
confidence: 99%
“…It is interesting to note that a survey performed by the Canadian Association of Oral and Maxillofacial Surgeons revealed that most of the respondents performed palatal infiltration in most patients requiring maxillary exodontia. 391 This shows that some academic discussions about the benefit or burden of different procedures might be of limited clinical importance for clinicians.…”
Section: Oral Medicine and Oral Surgerymentioning
confidence: 99%